Star Wars, the Clone wars : operation : huttlet - Filipek, Steele, 1984- (New York : Grosset & Dunlap, 2008)
Jedi Knight Anakin Skywalker, along with his Padawan Ahsoka Tano go on a mission to rescue Jabba the Hut's son, Rotta the Hutlet, after Rotta is kidnapped by the evil Count Dooku.
"Based on the movie Star wars: The clone wars."
"Lucas books."
3.6
K-3
Keywords: Vader, Darth (Fictitious character) -- Juvenile fiction; Kidnapping -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Vader, Darth (Fictitious character) -- Fiction; Kidnapping -- Fiction; Imaginary wars and battles -- Fiction; Vader, Darth (Fictional character) -- Fiction; Kidnapping -- Fiction; Imaginary wars and battles -- Fiction; Movie novels